Role of sorbents in early growth of barley under copper and benzo(a)pyrene contaminated soils - Anatoly Barakhov; Natalia Chernikova; Tamara Dudnikova; Andrey Barbashev; Svetlana Sushkova; Saglara Mandzhieva; Vishnu Rajput; Rıdvan Kızılkaya; Elizaveta Konstantinova; Dmitry Bren; Tatiana Minkina (Eurasian Journal of Soil Science, 2023)
In modern economic and industrial realities, agricultural lands are often located next to industrial areas, which leads to soil contamination and, as a result, agricultural products with pollutants. Pollution of soils and plants by several pollutants of various nature has acquired huge proportions. There is a threat of migration of dangerous ecotoxicants, including heavy metals and benz[a]pyrene, one of the main persistent compounds, a marker of PAH soil contamination, along trophic chains that may be dangerous to public health. This study examines the use of various types of mineral sorbents (Tripoli, Brown coal, Diatomite) and mineral sorbents (Biochar, Granular activated coal) to reduce the toxic effects of pollutants on the sources of anthropogenic emissions of heavy metals and polycyclic aromatic hydrocarbons adjacent to the sources. Using scanning electron microscopy, it was found that the sorbents have a high specific surface area. With the help of phytotesting in combined contaminated soils, the optimal dose of sorbent administration was determined at the level of 1% and 2% for various pollution variants. In addition, the analyzed sorbents are ordered by the effect of reducing the phytotoxicity of combined soil pollution. It was found that the introduction of sorbents into contaminated soil contributed to an increase in the morphometric parameters of the test culture - barley (Hordeum sativum distichum), which confirms the effectiveness of the sorption remediation of jointly contaminated soils with heavy metals and benz(a)pyrene.